Media phraseology and the category of expressiveness: stylistic interdependencies - Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article describes one of the key categories of media phraseology – the category of expressiveness. The author analyses a media phraseological unit (idiom) as a verbal unit of a media text in the context of a media linguistic approach – an innovative direction of modern philology. The scientific article is a continuation of a series of publications about the categories of modern phraseology and stylistic functions that a phraseological unit (idiom) performs in different types of media (web and print). A media phraseological unit (idiom) is considered as a unit which has signs of evaluation, emotionality, intertextuality, structural integrity and idiomaticity, which gives media  text figurativeness and expressiveness. The author focuses on the traditional and new phraseological units (idioms) that arise in mass consciousness under the influence of expression. The analyzed modern theories about a phraseological unit in the context of the functional approach – a broad interpretation of the language unit as universals of mass media communication – make it possible to objectify the stylistic potential of a phraseological unit (idiom) in media text using expressiveness. The material collected to “New  words  and  phraseology  in Ukrainian  media” (2016–2018) professionally compares and interprets потрібно написати, що саме with attention to extra- and intralingual features of media communication. This helps the author to prove that expressiveness is one of the dominant factors for the entry of new words into the Ukrainian mass verbal reality. To objectify scientific proofs and their media linguistic interpretation we use illustrative material (advertising, television, radio, Internet), on the example of which we analyze a broad stylistic potential of expression in phraseology. We note that the category of expressiveness in research perspective should be regarded as universal in terms of phraseology, particularly, in media communication.
Keywords: media phraseological unit (idiom), neolinguistics, media linguistic analysis, expressiveness.